(3GdJHUQIs - (3Ydj Hf eMeO GdQHYj, CHh GdMSf, GdeYQha HGddNej, J (B478 (3g` s; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj,J (B191 (3g` s
(3ChdgG (B:s
(3cJGH GdTgGOGJ GdChd s
(3BNQgG (B:s
(3HGdcdGe ai TgGOI GdEeGe hGdbGVi hcJGH bGVmi Edi bGmV hef jbje GdMO hgh BNQ cJGH GdQLe s
(3LRA ef fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3JYdjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B681s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs